Reproductive Factors and Risk of Ovarian Cancer - Schüler, S.; Ponnath, M.; Lattrich, C.; Ortmann, O. (TumorDiagnostik & Therapie, 2013)
Ovarian epithelial cancer (OEC) is the most lethal gynaecological malignancy and the sixth most common cancer among women in industrialised countries. This review summarises the current knowledge on the role of reproductive factors for the development of OEC. Recent studies have shown that OECs represent a diverse group of cancers. This is partly reflected in the results of epidemiological and clinical studies which have investigated the impact of various reproductive factors on the risk of developing OEC. Fewer ovulatory cycles, parity and lactation were found to decrease the risk for OEC, whereas the association between infertility and ovarian cancer has not yet been fully elucidated and further investigation is required. None of the proposed hypotheses on the development of ovarian cancer fully explains the epidemiological and clinical findings of the association between reproductive factors and OEC development. Further research is warranted which would focus more on the clinical and genetic diversity of OECs to obtain a better understanding of the pathogenesis.
Keywords: reproductive factors; ovarian malignancy; parity; lactation; infertility; PCO syndrome